Analisis Indikator Instrumen Kecemasan (Library Anxiety) Dengan Metode Confirmator Factor Analysis di Library and Knowledge Center @Senayan - Arief, Noor; Maulidya, Bella Septi; Erika, Erika (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2024)
Background: Understanding the characteristics of library users is crucial to identifying library anxiety and improving user experience and the effectiveness of information searching. Library anxiety can stem from various factors, including user perceptions, library facilities, and services.Objective: This study aimed to determine the accuracy and similarity of questionnaire indicators on anxiety instruments using Confirmatory Factor Analysis (CFA). The focus was limited to evaluating the indicators of library anxiety instruments.Methods: A quantitative approach was employed using CFA to analyze the validity and reliability of the indicators related to library anxiety. The study analyzed responses from users of the Library and Knowledge Center @Senayan.Results: The findings showed that library anxiety did not stem from the library itself or its staff. Instead, the LA10 indicator (the use of lockers) revealed that while users felt safe using lockers, they experienced inconvenience due to carrying many items. Meanwhile, indicators LA11 (library design) and LA12 (temperature and air quality) did not meet the criteria. During the study, the temperature and air quality were suboptimal but were repaired by December 2024. The library design is currently under renovation planning with an improved layout.Conclusion: This study highlights the importance of understanding user perceptions in addressing library anxiety. Improvements in facilities, including lockers, temperature, air quality, and library design, play a significant role in reducing anxiety and enhancing user satisfaction.